A Test System of Rock and Coal Specimen Creep Property Under Gas-liquid Supercharging - ZHANG Shaohua, SONG Wanxin, GAO Jie, QIU Haisheng (Meikuang Anquan, 2020)
A set of uniaxial compression creep test system for coal and rock is developed according to the principle of pneumatic control. The test system contains three parts: pneumatic control system, pressure system and automatic data acquisition system, and the validation experiments last as long as 22 days based on the test system. The results show that the applied load is very stable in the whole creep test period, and the applied load error fluctuates within 0.05 MPa in different stages of loading. The system has the advantages of small size, easy operation, low cost, automatic data acquisition and processing.